Enhancing Language Learning through Artificial Intelligence: An Analysis of Key Pedagogical Themes - Amanda; Agresti, Leli; Nabila, Ni Nyoman Diah; Auliana, Senela; Fauzi, Iwan (Pusat Kajian Bahasa Daerah & Budaya, 2026)
This study explores the benefits of Artificial Intelligence (AI) in language learning, particularly within English as a Foreign Language (EFL) contexts. Using a literature review method, the research examines previous studies to identify how AI supports the learning process. The findings reveal five main benefits: personalized and adaptive learning, increased learner motivation and engagement, autonomous and flexible study opportunities, real-time feedback, and instructional support for teachers. These results suggest that AI can address various limitations in traditional classrooms, such as large class sizes, lack of individual attention, and limited feedback. By enhancing accessibility and efficiency, AI tools help create more responsive and student-centered learning environments. The study concludes that the thoughtful integration of AI can significantly improve language instruction and provide long-term benefits for both learners and educators.